Public health measures and dignity in tension in professional hair care during the COVID-19 pandemic: A lesson for future pandemics - Nicola BRAGAZZI; Giuseppe TAINO; Tiziana GAZZOLDI; Irene TAINO; Francesco CHIRICO (GIornale Italiano di Psicologia e Medicina del Lavoro)
Professional hair care has generally not been considered a critical service and function during the COVID-19 pandemic. However, the lack of professional hair care services due to closed salons and the provision of home haircuts (or lack of) has the potential to impact human dignity – a concept linked to both ethics and legislation. Additionally, existing data sets regarding the transmission of COVID from positive stylists to their clients do not justify the closure of hair salons during the pandemic. Supporting the stance of the German and Italian governments, we argue for continued professional hair care services in salons and via home visits, incorporating a COVID safety protocol that includes preventive measures to protect workers and clients. This protocol can also accommodate clients unable or unwilling to be vaccinated. We also argue for the recommended vaccination of hair salon employees due to their key role in delivering professional hair care as an “essential service.”